Toxic Parenting and Mental Health Among Adolescents - Suci Anggriani Albakir; Ridha Hafid; Siti Hajar Salawali (Sarana Ilmu Indonesia (salnesia), 2026)
Adolescence is a transitional period that is vulnerable to various emotional and psychological changes, requiring a healthy family environment. One factor influencing adolescents’ mental health is parental parenting style. Toxic parenting is a negative parenting practice that can adversely affect adolescents' psychological well-being. This study aimed to examine the relationship between toxic parenting and mental health among adolescents at SMP Negeri 1 Limboto. The research used a quantitative approach with a cross sectional design and involved 82 subjects selected through proportional random sampling techniques. The characteristics of subjects include age, gender, class, parents' marital status, parents' education, parents' occupation, parents' income, and history of bullying. The research instruments included a toxic parenting questionnaire and the Strengths and Difficulties Questionnaire (SDQ). The results showed that most teenagers experienced moderate levels of toxic parenting (65.9%) and had mental health in the borderline category (48.8%). The results of the Chi-square test showed that there was a significant relationship between toxic parenting and adolescent mental health at SMP Negeri 1 Limboto with a Pearson Chi-Square value of 12.551 and a p-value of 0.002 (<0.05). In conclusion, toxic parenting was associated with adolescent mental health, and parents should adopt positive parenting and open communication.